Insulin-like Growth Factors may be Markers of both Traumatic Brain Injury and Fear-Related Stress. (1st July 2021) - Corne, Rémi; Besson, Valérie; Ait Si Slimane, Sofiane; Coutan, Mathieu; Palhas, Marta L.C.; Shen, Fang Xue; Marchand-Leroux, Catherine; Ogier, Michaël; Mongeau, Raymond
Highlights: Plasma IGF1 and IGF2 levels are most decreased after TBI in conditions of stress. Brain IGF1 level is increased in both the acute and chronic phases of TBI. TBI alters brain IGF2 staining in both the acute and chronic phases of TBI. Acutely, craniotomy and TBI alter brain but not plasma IGF1 or IGF2. Plasma IGF1 and IGF2 levels do not necessarily reflect changes in brain IGF system after TBI. Abstract: Insulin-like growth factors (IGF) are potent neurotrophic and neurorepair factors that were recently proposed as biomarkers of traumatic brain injury (TBI) and associated psychiatric comorbidities, in particular post-traumatic stress disorder (PSTD). We tested the hypothesis that the IGF system is differentially deregulated in the acute and early chronic stages of TBI, and under acute stress. Plasma and brain IGF1 and IGF2 levels were evaluated in mice 3 weeks and 3 days after a controlled cortical impact (CCI)-induced mild-to-moderate TBI. The effects of conditioned fear on IGF levels and its interaction with TBI (TBI followed, 3 weeks later, by fear-inducing procedures) were also evaluated. In the plasma, IGF1 decreased 3 weeks post-TBI only (−9%), whereas IGF2 remained unaffected. In the brain, IGF1 increased only in the cortex and hippocampus at 3 weeks post-TBI (up to +650%). At 3 days, surpringly, this increase was more diffuse and more important in sham (craniotomized) animals. Additionally, IGF2 immunostaining in brain ventricles was reorganized in TBI animals at both post-TBI stages. Conditioned fear exposure did not influence the effects of early chronic TBI on plasma IGF1 levels, but reduced plasma IGF2 (−6%) levels. It also dampened the effects of TBI on brain IGF systems, but brain IGF1 level and IGF2 tissue distribution remained statistically different from controls under these conditions. In co-exposed animals, DNA methylation increased at the hippocampal Igf1 gene promoter. These results show that blood IGF1 and IGF2 are most reduced in the early chronic phase of TBI and after exposure to a stressful event, and that the brain IGF system is up-regulated after TBI, and more so in the acute phase.